Lean Six Sigma aplicado en la mina Santa Luisa para reducir el costo de transporte de mineral - Rosas Rojas, Julio Junior (2023)
This thesis has been developed at the Santa Luisa mine during the 2022 period, which analyzes the operating costs and the unit cost of mineral transportation, as well as the application of the Lean Six Sigma philosophy to reduce their cost. That is why we proceeded to carry out an analysis of the unit costs that are directly incurred in the transfer of ore, from inside the mine to the surface; resulting in a variation of more than 22% between the comparative costs of the scheduled production and the forecast production, it is also important to make known that having proposed the change of unit for the transfer of ore and increasing the investment, the results obtained for the unit cost were very favorable which allowed us to advance with the improvement proposal and determine the other influential factors that are carried out within a process such as: Ishikawa diagram, Pareto, Control charts, Scatter charts, Sigma Level , Process Capacity, among other statistical tools used. It should be noted that during the analysis a 5-year forecast was made, considering the depreciation and salvage value of the equipment, as well as the use of different economic engineering tools to determine if the proposed future project is profitable or not.